Tinjauan Waktu Pelaksanaan Pekerjaan Renovasi Gedung Rawat Inap RS Wahidin Sudirohusodo Makassar - Fadli, Dwi; Abduh, Muh. Natsir; Mulyani, Savitri Prasandi (Jurnal Penelitian Teknik Sipil Konsolidasi, 2026)
Construction projects are often faced with challenges in terms of managing time, costs and quality. This research discusses "A review of the time for the renovation work of the Wahidin Sudirohusodo Hospital Makassar Inpatient Building" which aims to identify activities that are on the critical path and the time duration used for the project. This research uses a type of quantitative research where the data used includes time schedule (Kuva S) and other project data. The method used in this research is the Critical Path Method (CPM). The CPM method can identify the critical path and provide a logical picture of the sequence of work and time required for each activity on the project. The research results show that by using the CPM method in the inpatient building renovation project at Wahidin Sudirohusodo Makassar Hospital, it is known that the critical path is in activities that have a total float value of 0 (zero). Based on calculations, the project's scheduled duration is 161 days, but after being analyzed using the CPM method, the project can be completed in 154 days. Thus, it can be seen after analyzing using the CPM method that the time comparison with the previously scheduled project duration is 7 days.